An Overview of Mathematical Beauty in Poetry - Adhikari, Iswar Mani (International Journal of Operational Research/Nepal, 2023)
It is conceived that mathematics deals with the backbreaking concept, controlled and coordinated by minds, whereas poetry deals with the interesting aspects, controlled and coordinated by hearts, and are rarely correlated. However, it is not so, in general. Mathematics works to discover where poetry tries to create, and they have bilateral connections. Mathematician, like a painter or a poet, makes beautiful patterns of colors or words harmonically to integrate eternal beauty. This work attempts a pathway between these seemingly paradoxical disciplines working with different mathematical patterns, their existence and applications, structures, and their beauties related to poetry.